Sex-specific associations of ceramides with cardiopulmonary fitness in the general population. (11th May 2021) - Zatloukal, J; Markus, MRP; Ewert, R; Glaeser, S; Friedrich, N; Voelzke, H; Felix, SB; Doerr, M; Bahls, M; Gross, S
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): German Federal Ministry of Education & Research (BMBF) Introduction: According to the WHO 17.9 million people die because of cardiovascular diseases (CVD) each year, being the 3rd leading cause of death worldwide. Low cardiorespiratory fitness (CRF) is an important risk factor for CVD. Recent research showed that long-chain unsaturated ceramides are associated with higher risk of cardiovascular events, thus identifying ceramides as a potential novel and independent risk factor. However, not all ceramides are equal. We previously showed beneficial effects of very-long-chain ceramides (i.e. C24:0 and C24:0/C16:0 ratio) with higher concentrations being inversely associated with all-cause mortality and CVD events. Purpose: We would like to investigate, if ceramides mediated their effects on developing CVD by affecting CRF. Therefore, we explored the association of three specific ceramides (C16:0, C22:0 and C24:0) and their ratios with different parameters of CRF. Methods: We used data of the population-based Study of Health in Pomerania (SHIP-1) from North Germany (N: 1, 247/men: 583, median age: 50.8 years/women: 664, median age: 50.2 years). Ceramides and CRF were assessed by LC/MS assay and symptom-limited cardiopulmonary exercise testing, respectively. VO2peak, VO2@AT, Wmax and respective indexing per kg body weight were used as outcomes. We used sex-stratified, multiple adjusted linear regression models. Participants with asthma, chronic lung disease, LVEF < 40% and cancer were excluded. Results: In men, a 1-unit higher C24:0/C16:0 ratio was associated with higher VO2peak/kg (0.199 ml/min/kg [95% CI: 0.032, 0.365], P = 0.019), Wmax (1.368 W [0.033, 2.404], P = 0.010) and Wmax/kg (0.018 W/kg [0.007, 0.029], P = 0.002). In addition, a 1 µg/ml higher C24:0 concentration was related to greater Wmax/kg (0.054 W/kg [0.009, 0.099], P = 0.018). In women, a 1-unit greater C24:0/C16:0 ratio was associated with greater VO2peak (8.603 ml/min [0.019, 17.013], P = 0.045), VO2peak/kg (0.186 ml/min/kg [0.054, 0.319], P = 0.006), VO2@AT/kg (0.136 ml/min/kg [0.040, 0.231], P = 0.005) as well as higher Wmax/kg (0.015 W/kg [0.004, 0.026], P = 0.007). Furthermore, a 1 µg/ml higher C16:0 concentration was related to lower Wmax (-55.447 W [-101.775, -9.119], P = 0.019) and Wmax/kg (-0.736 W/kg [-1.341, -0.130], P = 0.017). Conclusions: We report sex-specific associations between ceramides and CRF. In women, C24:0/C16:0 ratio was associated with more CRF parameters than in men. Furthermore, the single species C16:0 was significantly associated with lower maximal power in women only, whereas in men the single species C24:0 was significantly associated with higher maximal power. The positive association of the C24:0/C16:0 ratio with maximal CRF capacity is in agreement with previous findings of beneficial effects on the risk for CVD events and mortality. Future studies should explore the reason for different sex-specific ceramide profiles and whether ceramides are causally mediating their effects on CVD through CRF.